INTRODUCTION OF MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN VOCATIONAL EDUCATION INSTITUTIONS (Innovative professional education, 2025)
The article justifies the necessity of integrating educational digital platforms into the modern learning process. It outlines the purpose, functionality, and significance of educational online services and electronic learning platforms in structuring the educational process.
Keywords: educational platform, information and communication technologies, online education, online service, online board, online program